Facile synthesis of Fe3O4@Au core–shell nanocomposite as a recyclable magnetic surface enhanced Raman scattering substrate for thiram detection. (2nd September 2019) - Han, Donglai; Li, Boxun; Chen, Yue; Wu, Tong; Kou, Yichuan; Xue, Xiaojing; Chen, Lei; Liu, Yang; Duan, Qian
Abstract: The Fe3 O4 @Au core–shell nanocomposites, as the multifunctional magnetic surface enhanced Raman scattering (SERS) substrates, were fabricated successfully by the seeds growth method based on the Fe3 O4 –Au core-satellite nanocomposites. The SERS properties of the Fe3 O4 –Au core-satellite nanocomposites and the Fe3 O4 @Au core–shell nanocomposites were compared using 4-aminothiophenol (4-ATP) as the probe molecule. It was found that Fe3 O4 @Au core–shell nanocomposites showed better SERS performance than Fe3 O4 –Au core-satellite nanocomposites. The Au shell provided an effectively large surface area for forming sufficient plasmonic hot spots and capturing target molecules. The integration of magnetic core and plasmonic Au nanocrystals endowed the Fe3 O4 @Au core–shell nanocomposites with highly efficient magnetic separation and enrichment ability and abundant interparticle hot spots. The Fe3 O4 @Au core–shell nanocomposites could be easily recycled because of the intrinsic magnetism of the Fe3 O4 cores and had good reproducibility of the SERS signals. For practical application, the Fe3 O4 @Au core–shell nanocomposites were also used to detect thiram. There was a good linear relationship between the SERS signal intensity and the concentration of thiram from 1 × 10 −3 to 1 × 10 −8 M and the limit of detection was 7.69 × 10 −9 M. Moreover, residual thiram on apple peel was extracted and detected with a recovery rate range of 99.3%. The resulting substrate with high SERS activity, stability and strong magnetic responsivity makes the Fe3 O4 @Au core–shell nanocomposites a perfect choice for practical SERS detection applications.